Effects of a physician-nurse-dietitian integrated management model education program on serum phosphorus in maintenance hemodialysis patients with hyperphosphatemia - ZENG Qiao; HUANG Jiang-ming; SHI Hong-bin; ZHONG Qing-rong (Linchuang shenzangbing zazhi)
Objective To explore the effects of a physician-nurse-dietitian integrated management model education program on serum phosphorous control in maintenance hemodialysis(MHD) patients with hyperphosphatemia.Methods Thirty hemodialysis patients having refractory hyperphosphatemia from September 2018 to March 2019 in Department of Nephropathy of our hospital were recruited in this study. A physician-nurse-dietitian integrated management model was adopted to intervene the patients for 3 months(90 days). The patients’ hyperphosphate miarelated knowledge, nutritional status, dietary intake, laboratory test results of serum phosphorous level, serum calcium level and albumin were assessed and compared with those at baseline. Results The score of hyperphosphatemia knowledge questionnaire after intervention was significantly higher than that before intervention(P<0.01), and the serum phosphorous level decreased significantly(P<0.01) after the intervention. The nutritional status assessment indicators, serum calcium, albumin and iPTH level were stable during the study period. Both their dietary calories did not change; while their dietary protein, phosphorous and phosphorous/protein ratio were decreased significantly compared to those before intervention(P<0.05).Conclusions The physician-nurse-dietitian integrated management model education can improve the hyperphosphatemia related knowledge of MHD patients, reduce serum phosphorous level and dietary phosphorous intake without malnutrition.